2006
DOI: 10.1007/s00253-006-0517-0
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of resin acid derivatives

Abstract: The wide potential of resin acids as bioactive agents gave rise to a growing effort in the search for new applications of the natural forms and their derivatives. In some of these compounds, the antimicrobial activity is associated to the presence in the molecules of functional groups such as the hydroxyl, aldehyde, and ketone or to their cis or trans configurations. The resin acid family covers a spectrum of antimicrobial activities against several microorganisms, from bacteria to fungi, in which the mode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(52 citation statements)
references
References 21 publications
1
47
0
4
Order By: Relevance
“…Meanwhile the Escherichia coli bacteria samples showed no activity. This goes along with research conducted by Savluchinske-Feio et al (2006) who reported that resin of Pinusponterosa effective against Gram-positive bacteria Bacillus subtilis (ATCC 9372) and Brevibacteriumammoniagenes (ATCC 6872) with a paper disc method. Instead, the resin of Pinusnigra ineffective in testing fungi and Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile the Escherichia coli bacteria samples showed no activity. This goes along with research conducted by Savluchinske-Feio et al (2006) who reported that resin of Pinusponterosa effective against Gram-positive bacteria Bacillus subtilis (ATCC 9372) and Brevibacteriumammoniagenes (ATCC 6872) with a paper disc method. Instead, the resin of Pinusnigra ineffective in testing fungi and Gram-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Diterpene antimicrobial activity against certain microorganisms associated with the presence of the group in the molecule functional groups such as carboxyl, hydroxyl, aldehyde or ketone and among other groups. The ability of these functional groups act as donor or acceptor of hydrogen by microbial targets, and the importance of the position of the functional groups in the framework of the hydrocarbon causes the formation of several important structure-activity relationships (Savluchinske-Feio, et al, 2006). Antimicrobial diterpenoids can act on multiple biochemical targets of the microorganisms and it has been suggested that the activity of these compounds results from their ability to cross or damage microbial cell membranes due to their amphiphilic nature.…”
Section: Resin / Essential Oilsmentioning
confidence: 99%
“…Certains des acides résiniques identifiés ont montré des activités chimiopréventive (Minami et al, 2002) et antibactérienne (Savluchinske-Feio et al, 2006). Les composés majoritaires des fractions PRHex 2 et PRHex 2.7 n'ont pu être identifiés grâce à cette banque.…”
Section: Travaux D'isolement Sur La Fraction Prhex 2 Del 'Extrait Hexaneunclassified
“…Given the chemical composition of conifer needles, it can be expected that the observed fungistatic effect corresponds to the presence of resinous substances that contain mainly turpentine (volatile fraction-mostly monoterpene olefins with some sesquiterpenes) and rosin (non-volatile fraction-mostly resin acids) [32,33]. The antimicrobial activity of both these fractions was indicated in numerous studies e.g.…”
Section: Growth Of the A Niger Mycelium Depending On The Compositionmentioning
confidence: 99%